Structures of chitosan used for bone regeneration in vivo: a literature review (Research, Society and Development, 2020)
Introduction: Biomaterials are synthetic or natural materials that aim to replace and / or treat any component of the organism. Among the different types of biomaterials, the most successful reported in the literature is the one of autogenous origin, however there is the disadvantage of creating a second surgical wound for its extraction. One of the challenges in the current medical-dental field is bone regeneration by means of biomaterials that are not of autogenous origin. In this context, the use of biopolymers such as chitosan extracted from chitin of crustacean shells has been studied as an alternative for bone regeneration therapies. Objective: To verify the presence in the literature about the potential for bone regeneration in vivo of chitosan, in national and international journals. Materials and methods: Search for information in the databases PubMed, Lilacs, Scielo, Periodicals Capes and Google Scholar in the period from 2009 to 2019. Result: In this context, most positive results were found for bone regeneration or potential for bone healing of isolated or associated chitosan structures. Conclusion: It is concluded that the use of chitosan in bone repair presents itself as a promising therapy.